Impact of circuit training on total distance covered and VO2 max in national-level women cricket players of Bangladesh - Farjana Akter Boby; Nirmal Michael Salvi; Md. Zafiroul Islam; Wilson Vinu; Bekir Erhan Orhan; Robert Citozi; Ibnu Noufal Kambitta Valappil; Karuppasamy Govindasamy; Debajit Karmakar; Vlad Adrian Geantă (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background and Study Aim: The study investigates the effect of circuit training on the cardiorespiratory fitness of national-level female cricket players in Bangladesh. Thirty players were randomly selected from different playing positions (batters, bowlers, and all-rounders) and underwent a pre-and post-test design with no control group.